2018
DOI: 10.1159/000493846
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone and Dexamethasone Phosphate Entry into Perilymph Compared for Middle Ear Applications in Guinea Pigs

Abstract: Dexamethasone phosphate is widely used for intratympanic therapy in humans. We assessed the pharmacokinetics of dexamethasone entry into perilymph when administered as a dexamethasone phosphate solution or as a micronized dexamethasone suspension, with and without inclusion of poloxamer gel in the medium. After a 1-h application to guinea pigs, 10 independent samples of perilymph were collected from the lateral semicircular canal of each animal, allowing entry at the round window and stapes to be independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Importantly, the RWM is semipermeable, allowing passage of a wide range of materials including antibiotics, local anesthetics, toxins, and albumin . RWM permeability is affected by many factors, including the size, configuration, concentration, liposolubility, and electrical charge of the diffusing molecules, as well as properties of the RWM itself such as its thickness . RWM permeability also decreases in pathological states such as otitis media due to the inflammatory process.…”
Section: Anatomic Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the RWM is semipermeable, allowing passage of a wide range of materials including antibiotics, local anesthetics, toxins, and albumin . RWM permeability is affected by many factors, including the size, configuration, concentration, liposolubility, and electrical charge of the diffusing molecules, as well as properties of the RWM itself such as its thickness . RWM permeability also decreases in pathological states such as otitis media due to the inflammatory process.…”
Section: Anatomic Barriersmentioning
confidence: 99%
“…14 RWM permeability is affected by many factors, including the size, configuration, concentration, liposolubility, and electrical charge of the diffusing molecules, as well as properties of the RWM itself such as its thickness. [14][15][16] RWM permeability also decreases in pathological states such as otitis media due to the inflammatory process. For these reasons, diffusion across the RWM is often inconsistent and associated with unreliable therapeutic dosing, particularly during intratympanic injection.…”
Section: Round Window Membranementioning
confidence: 99%
“…The round window membrane (RWM) is the most accessible of these structures; absorption of drugs through the RWM is dependent upon permeability properties and the contact duration of the applied drug substances. For instance, RWM permeability is markedly affected by the presence of additives such as membrane permeation enhancers (Li et al, 2018) and preservatives (Mikulec et al, 2008), certain attributes of the pharmacological agent such as molecular weight (Chelikh et al, 2003) and chemical properties (Salt et al, 2018; Salt and Plontke, 2018). Animal studies as well as computer simulations have demonstrated that prolonging the drug contact duration of aqueous solutions with the round window membrane results in increased drug levels in the inner ear (Plontke and Salt, 2006; Plontke et al, 2007a).…”
Section: Pharmacokinetic Considerations Of the Inner Earmentioning
confidence: 99%
“…We recently reported that dexamethasone-phosphate, the most common form of dexamethasone used for local treatment of the ear, has properties that make it quite unsuitable for local therapy of the ear (Salt et al, 2018). The polar phosphate group that makes the drug more soluble also makes this form of the drug substantially less permeable though the RW membrane than native dexamethasone, limiting the amount entering.…”
Section: Introductionmentioning
confidence: 99%
“…Within the ear it is then metabolized to the active form, dexamethasone, which is highly permeable through the blood-labyrinth barrier and is rapidly lost from perilymph. The high rate of dexamethasone elimination limits how far the drug spreads apically along the ear (Plontke et al, 2008; Salt et al, 2018). As a result, concentrations reaching the speech frequency regions of the human are calculated to be low (Liebau et al, 2017).…”
Section: Introductionmentioning
confidence: 99%